ANALISIS RENCANA PEMEKARAN KECAMATAN DI KABUPATEN SANGGAU PROVINSI KALIMANTAN BARAT (Studi Kasus di Kecamatan Meliau ) - Hubertus Leydin (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
One way of making public service closer to citizens in through providing service centres at subdistrict level. Large sub-disctricts should be blossomed so that service centres are not distant from citizens’ reach. For this purpose, people of 8 villages at Meliau sub-district plan to form a new subdistrict. The underlying legal basis for the blossoming is Internal Affairs Ministrial Decree No 4 Year 2000 regarding Guidelines for Sub-distrci Formation, which cover three main aspects: width of territory, demography and number of villages. Through the territorial management, it is expected that: (1) governmental span of control can be optimized and service institutions are closer to citizens, (2) Social security and good order can be achieved, (3) Social prosperity can be increased, and (4) development programs in all aspects can be accelerated.